2016
DOI: 10.1038/nature19320
|View full text |Cite
|
Sign up to set email alerts
|

High-molecular-weight organic matter in the particles of comet 67P/Churyumov–Gerasimenko

Abstract: The presence of solid carbonaceous matter in cometary dust was established by the detection of elements such as carbon, hydrogen, oxygen and nitrogen in particles from comet 1P/Halley. Such matter is generally thought to have originated in the interstellar medium, but it might have formed in the solar nebula-the cloud of gas and dust that was left over after the Sun formed. This solid carbonaceous material cannot be observed from Earth, so it has eluded unambiguous characterization. Many gaseous organic molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 31 publications
9
119
0
Order By: Relevance
“…COSIMA’s mass spectra of the organic matter in Kennith and Juliette are best represented by reference spectra of insoluble organic matter (IOM) in carbonaceous chondrites (Orgueil and Murchison); three aspects in which they are similar are that they both have high molecular weights, lack carbon-bearing ions with m / z ratios more than 50, and have lower H/C ratios. The COSIMA results call out the lack of lower molecular weight organics with higher H/C ratios including carboxylic acids, aliphatics, PAHs or amino acids [190]. This is in contrast to the frequent detection of carboxylic acids and aliphatic carbon in IDPs (e.g.…”
Section: Conspectus: Changing Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation
“…COSIMA’s mass spectra of the organic matter in Kennith and Juliette are best represented by reference spectra of insoluble organic matter (IOM) in carbonaceous chondrites (Orgueil and Murchison); three aspects in which they are similar are that they both have high molecular weights, lack carbon-bearing ions with m / z ratios more than 50, and have lower H/C ratios. The COSIMA results call out the lack of lower molecular weight organics with higher H/C ratios including carboxylic acids, aliphatics, PAHs or amino acids [190]. This is in contrast to the frequent detection of carboxylic acids and aliphatic carbon in IDPs (e.g.…”
Section: Conspectus: Changing Paradigmsmentioning
confidence: 99%
“…The Rosetta COSIMA instrument identifies in the coma of 67P a component of the dust that is high molecular weight organic matter [190], which is similar to the organic matter in IDPs [108] and UCAMMs [195]. Two 100 μm size regions, ‘Kennith’ and ‘Juliette’ are reported on and are representative of seven other particles.…”
Section: Ultracarbonaceous Antarctic Micrometeoritesmentioning
confidence: 99%
“…Further observations of glycine during flybys at different radial distances suggest a distributed source of glycine associated with dust [97]. Compositional analysis of dust particles collected in May 2015 shows evidence of calcium–aluminium-rich inclusions, previously found in stardust samples [132], and high-molecular-weight organic matter in dust grains collected in May and October 2015 [133], which was not observed in particles obtained earlier [66]. …”
Section: Development Of Cometary Activity Comparing With Pre-perihelmentioning
confidence: 86%
“…Initiated either in the ice phase (Colangeli et al 2004;Cottin et al 1999;Meinert et al 2012Meinert et al , 2016Strazzulla and Palumbo 1998;Vinogradoff et al 2013) or in the gaseous phase in the protosolar nebula (Nuth et al 2008), complex organic compounds are observed in carbonaceous chondrite (Martins 2011), micrometeorites, UltraCarbonaceous Antarctic micrometeorites (UCAMMs) and interplanetary dust particles (IDPs) (Clemett et al 1993;Dartois et al 2013;Matrajt et al 2013) and in comets (Capaccioni et al 2015;Elsila et al 2009;Goesmann et al 2015;Wright et al 2015;Fray et al 2016). The surfaces of comets, asteroids, and their fragments (i.e.…”
Section: Small Bodies and Exogeneous Sources Of Organic Compoundsmentioning
confidence: 99%